Characterizing colonic motility in children with chronic intractable constipation: a look beyond high‐amplitude propagating sequences. Issue 5 (12th February 2016) - Wessel, S.; Koppen, I. J. N.; Wiklendt, L.; Costa, M.; Benninga, M. A.; Dinning, P. G.
Abstract: Background: Children with chronic intractable constipation experience severe and long‐lasting symptoms, which respond poorly to conventional therapeutic strategies. Detailed characterization of colonic motor patterns in such children has not yet been obtained. Methods: In 18 children with chronic intractable constipation, a high‐resolution water‐perfused manometry catheter (36 sensors at 1.5‐cm intervals) was colonoscopically placed with the tip at the distal transverse colon. Colonic motor patterns were recorded for 2 h prior to and after a meal and then after colonic infusion of bisacodyl. These data were compared with previously published colonic manometry data from 12 healthy adult controls and 14 adults with slow‐transit constipation. Key Results: The postprandial number of the retrograde cyclic propagating motor pattern was significantly reduced in these children compared with healthy adults (children, 3.1 ± 4.7/h vs healthy adults, 34.7 ± 45.8/h; p < 0.0001) but not constipated adults (4.5 ± 5.6/h; p = 0.9). The number of preprandial long‐single motor patterns was significantly higher ( p = 0.003) in children (8.0 ± 13.2/h) than in healthy adults (0.4 ± 0.9/h) and in constipated adults (0.4 ± 0.7/h). Postprandial high‐amplitude propagating sequences (HAPSs) were rarely observed in children (2/18), but HAPS could be induced by bisacodyl in 16 of 18 children. Conclusions & Inferences: Children with chronic intractable constipation show a similar impaired postprandial colonic response to that seen in adults with slow‐transit constipation. Children may have attenuated extrinsic parasympathetic inputs to the colon associated with an increased incidence of spontaneous long‐single motor patterns. Abstract : Utilizing high‐resolution colonic manometry, in children with chronic intractable constipation, we have quantified the motor patterns prior to and after a meal. These data in children display similarities to adults with slow‐transit constipation, and like the constipated adults, we propose that in these children a possible neuropathy in the extrinsic parasympathetic inputs to the colon may exist.